Bio-syngas Production from Glycerol Dry Reforming over Cement Clinker-supported Nickel Catalyst - Hua, Chyn Lee; Jolius, Gimbun; Suzana, Yusup; Cheng, C. K. (2013)
This paper describes glycerol dry (CO2) reforming system for producing H2:CO mixture with ratios 1.0 to 2.0 suitable for downstream Fischer-Tropsch (FT) synthesis. Conventional glycerol steam reforming suffers from carbon deposition on catalysts, CO2 greenhouse gas production and high H2:CO product ratios. Glycerol dry reforming (GDR) is a new area with no prior publications. Significantly, thermodynamic predictions in previous work showed that GDR is able to produce 6.4 moles of syngas per mole of glycerol [Wang et al., 2009]. Ni-based catalysts have been widely used in industry due to its low cost compared to the noble metals but prone to coking. Coking can be alleviated or reduced by the introduction of strong Lewis base oxide such as CaO [Ruckensteina and Hu, 1995]. Cement clinker (CC) contains 63.28% CaO [Kurdowski, 2002], hence a natural choice as catalyst support. Most importantly, CC is abundantly available from cement industry in Malaysia and possesses high level of thermal stability. In this work, the reactivity of glycerol dry reforming over the CC-supported Ni catalyst, kinetic behaviour and type of carbon species deposited were reported.